2014
DOI: 10.1002/ar.23058
|View full text |Cite
|
Sign up to set email alerts
|

The Rabbit Brachial Plexus as a Model for Nerve Repair Surgery—Histomorphometric Analysis

Abstract: One of the most devastating injuries to the upper limb is trauma caused by the avulsion. The anatomical structure of the rabbit's brachial plexus is similar to the human brachial plexus. The aim of our study was to analyze the microanatomy and provide a detailed investigation of the rabbit's brachial plexus. The purpose of our research project was to evaluate the possibility of utilizing rabbit's plexus as a research model in studying brachial plexus injury. Studies included histomorphometric analysis of sampl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 25 publications
(27 reference statements)
2
12
0
Order By: Relevance
“…In all rabbits, the ulnaris nerve was consistently the largest nerve structure in this area. The same finding has been reported in dogs and cats 2,6 . In this approach, recently some researchers have been studying the ultrasound guided mid-humeral block of the radial, ulnar, median and musculocutaneous nerves (RUMM block) in dogs with success in orthopedic surgery 15 .…”
Section: Identification Of Individual Structures Was Possible Mainly Bysupporting
confidence: 89%
See 3 more Smart Citations
“…In all rabbits, the ulnaris nerve was consistently the largest nerve structure in this area. The same finding has been reported in dogs and cats 2,6 . In this approach, recently some researchers have been studying the ultrasound guided mid-humeral block of the radial, ulnar, median and musculocutaneous nerves (RUMM block) in dogs with success in orthopedic surgery 15 .…”
Section: Identification Of Individual Structures Was Possible Mainly Bysupporting
confidence: 89%
“…comparing our anatomic results with those of other studies performed with different species 2,6 . In our study, we observed that the roots of the brachial plexus (C5, C6, C7, C8 and T1)…”
Section: Identification Of Individual Structures Was Possible Mainly Bysupporting
confidence: 56%
See 2 more Smart Citations
“…For rabbits, this ratio is 0.59-0.63 at the root level, 0.62-0.65 at the trunk level, and 0.63 in the suprascapular nerve [44]. Comparison of these results with those obtained using healthy limbs appears to be sufficient to assess conduction ability.…”
Section: Discussionmentioning
confidence: 66%